Neuroimaging in dementia and Alzheimer's disease: Current protocols and practice in the Republic of Ireland. Issue 2 (May 2016) - Kelly, I.; Butler, M.-L.; Ciblis, A.; McNulty, J.P.
Abstract: Introduction: Neuroimaging plays an essential supportive role in the diagnosis of dementia, assisting in establishing the dementia subtype(s). This has significant value in both treatment and care decisions and has important implications for prognosis. This study aims to explore the development and nature of neuroimaging protocols currently used in the assessment of dementia and Alzheimer's disease (AD). Methods: An online questionnaire was designed and distributed to lead radiography personnel working in computed tomography (CT), magnetic resonance imaging (MRI) and positron emission tomography (PET) departments (n = 94) in both hospital-based and out-patient imaging centres in the Republic of Ireland. Results: Response rates for each modality ranged from 42 to 44%. CT, MRI, and PET were used to specifically diagnose dementia or AD by 43%, 40% and 50% of responding centres respectively. Of these, dementia-specific neuroimaging protocols were utilised in 33%, 50% and 100% of CT, MRI and PET centres respectively, with the remainder using either standard or other non-specific protocols. Both radiologists and clinical specialist radiographers participated in the development of the majority of protocols. The Royal College of Radiologists (RCR) guidelines were most commonly referenced as informing protocol development, however, none of the MRI respondents were able to identify any guidelines used to inform MR protocol development. Conclusion: Currently there is no consensus in Ireland on optimal dementia/AD neuroimaging protocols, particularly for PET and MRI. Similarly the use of validated and published guidelines to inform protocols is not universal. Highlights: We examined the nature of neuroimaging protocols for dementia and Alzheimer's disease in Ireland. Dementia or Alzheimer's disease-specific protocols were used by between 33 and 100% of centres depending on modality. Stated dementia-specific protocols were identical for CT whereas these varied for MRI and PET. Standardisation of neuroimaging protocols is required to allow novel biomarkers to be incorporated into clinical practice.